Epicureanism a very short introduction - Wilson, Catherine 1951- (Oxford University Press, 2015)
This very short introudction corrects the prevalent view of Epicureanism that often conjures up ideas of tasty delights and hedonism. Wilson explains the philosophical and scientific ideas of Epicurus and his followers and the legacy of Epicureanism on later European thought
Includes bibliographical references and index
Keywords: Epicureans (Greek philosophy); Epikureismus